1986
DOI: 10.1002/aja.1001750212
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy of cell surface antigens labeled with colloidal gold

Abstract: A method is described and discussed that permits the specific labeling of the surface of prefixed cells with the colloidal gold marker viewed with the scanning electron microscope. Its value depends exclusively on the use of backscattered electron imaging. Its advantages include the possibility of preserving the surface features of the labeled cells, the ease with which specificity can be established, the possibility of making total counts of the labeled surface antigenic sites, and the possibility of achievin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…This prefix procedure was employed to prevent receptor endocytosis and loss of surface structure (de Harven, 1987;de Harven and Soligo, 1986). Thereafter, the slide was placed for 5 rnin in 0.1% glycine in PBS and then bathed twice for 5 rnin in PBS containing serum proteins to block nonspecific adsorption of the primary and/or secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This prefix procedure was employed to prevent receptor endocytosis and loss of surface structure (de Harven, 1987;de Harven and Soligo, 1986). Thereafter, the slide was placed for 5 rnin in 0.1% glycine in PBS and then bathed twice for 5 rnin in PBS containing serum proteins to block nonspecific adsorption of the primary and/or secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary electron image (SEI) mode, backscatter electron image (BEI) mode, and mixed image (SEI/ BEI) mode were used to examine immunogold-labeled cells (de Harven et al, 1984;de Harven and Soligo, 1986;de Harven, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…We have studied the binding of such an antibody on A,, A,, A,, A, and A,, erythrocytes, using the backscattered electron imaging (BEI) mode of a scanning electron microscope. Bound antibody was revealed by anti-antibody conjugated to colloidal gold particles, which can be conveniently visualized because of their intense backscatter electron signal (11,12,13). Preliminary results of this study have been reported elsewhere (14).…”
mentioning
confidence: 90%
“…The cells in the negative control wells were incubated with DMEM and 10 mg . [25] was followed. The cells, grown on coverslips or micropore membranes were rinsed twice in 0.01 M PBS and lightly "prefixed" for 10 min in freshly prepared 0.2% glutaraldehyde solution with 4% sucrose buffered in 0.01 M PBS (pH 7.2).…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%